2018
DOI: 10.1007/s13205-018-1235-x
|View full text |Cite
|
Sign up to set email alerts
|

A combined pathway of organogenesis and somatic embryogenesis for an efficient large-scale propagation in date palm (Phoenix dactylifera L.) cv. Mejhoul

Abstract: An efficient regeneration system via a combined pathway of organogenesis and somatic embryogenesis was developed for date palm ( L.) cv. Mejhoul. Adventitious buds were obtained from shoot-tip explants with a frequency of 53.3% after 9 months of culture: 6 months on half-strength Murashige and Skoog (MS/2) medium containing 14.2 µM indole-3-acetic acid (IAA), 13.4 µM 1-naphthaleneacetic acid (NAA) and 0.5 µM 6-(dimethylallylamino) purine (2iP), and 3 months on MS/2 medium supplemented with 1.1 µM IAA, 1.1 µM N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Such explants, which are pathogen-free and available throughout the year, were successfully used previously in other Moroccan date palm cultivars. 8,9,11 The findings of the present investigation indicated that adventitious bud explants have a high embryogenic potential, with a rate of up to 89%. This is in good agreement with our previous studies.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Such explants, which are pathogen-free and available throughout the year, were successfully used previously in other Moroccan date palm cultivars. 8,9,11 The findings of the present investigation indicated that adventitious bud explants have a high embryogenic potential, with a rate of up to 89%. This is in good agreement with our previous studies.…”
Section: Discussionmentioning
confidence: 50%
“…10 Recently, explants derived from plant material maintained in vitro, such as adventitious buds, leaves, roots were also used, and a high embryogenic potential of adventitious bud explants was reported. 8,11 Such explants are pathogen-free, available independently of seasons and allow to avoid excessive use of offshoots and spathes. 8 The main objective of the present work was to develop a regeneration system for date palm cv.…”
Section: Introductionmentioning
confidence: 99%
“…Results clearly showed that combinations of picloram with 2ip and BA gave the highest response for embryonic culture and globularization. Similarly, inducing somatic embryogenesis from adventitious bud segments of Mejhoul shoot tips was encouraged by different concentrations of picloram [ 36 ]. The surpassed medium for somatic embryogenesis induction (70%) was MS medium supplemented with 10.8 mg/l picloram and 1.0 mg/l 2iP.…”
Section: Discussionmentioning
confidence: 99%
“…When a PGR stimulates explants and calluses, the internal intrinsic hormones produce feedback [12] and induce a callus to form an embryonic callus [13,14]. In many cases, specific combinations and proportions of auxin and cytokinin can effectively induce embryonic callus or directional differentiation of organs [15,16]. Somatic embryogenesis technology plays an important role in the preparation of artificial seeds and the genetic improvement of garden plants.…”
Section: Introductionmentioning
confidence: 99%